Clinical Features, Outcomes, and Response to Corticosteroid Treatment of Acute Tubulointerstitial Nephritis: A Single-Centre Retrospective Cohort Study in the Czech Republic - Oskar Zakiyanov; Yaprak Ḉaḡlar; Romana Ryšavá; Eva Jančová; Dita Maixnerová; Doubravka Frausová; Tomáš Indra; Eva Honsová; Vítězslav Kříha; Ivan Rychlík; Vladimír Tesař; Věra Čertíková Chábová (Karger Publishers, 2023)
Introduction: Acute tubulointerstitial nephritis (ATIN) is a well-recognized cause of acute kidney injury (AKI) due to the tubulointerstitial inflammation. The aim of this study was to explore the clinical features, outcomes, and responses to corticosteroid treatment in patients with ATIN. Methods: Patients with biopsy-proven ATIN, who were diagnosed between 1994 and 2016 at the Department of Nephrology, Charles University, First Faculty of Medicine, and General University Hospital in Prague, were included in the study. Patient demographics, the aetiological and clinical features, the treatment given, and the outcome at 1 year of follow-up were extracted from patient records. Results: A total of 103 ATIN patients were analysed, of which 68 had been treated with corticosteroids. There was no significant difference in the median serum creatinine 280 (169-569) µmol/L in the conservatively managed group versus 374 (249-558) µmol/L in the corticosteroid-treated group, p = 0.18, and dependence on dialysis treatment at baseline at the time of biopsy (10.3 vs. 8.6%). During the 1 year of follow-up, those ATIN patients who had been treated with corticosteroids did better and showed greater improvement in kidney function, determined as serum creatinine difference from baseline and from 1 month over 1-year period (p = 0.001). Conclusions: This single-centre retrospective cohort study supports the beneficial role of the administration of corticosteroid therapy in the management of ATIN.